Electroacupuncture for acute gouty arthritis: a systematic review and meta-analysis of randomized controlled trials - Ni, Zhichao; Xiao, Qinwen; Xia, Zihao; Kuang, Kunlin; Yin, Bingzun; Peng, Dezhong (Frontiers in Immunology, 2024)
Acute gouty arthritis (AGA) is a metabolic disorder in which recurrent pain episodes can severely affect the quality of life of gout sufferers. Electroacupuncture (EA) is a non-pharmacologic therapy. This systematic review aimed to assess the efficacy and safety of electroacupuncture in treating acute gouty arthritis. We searched eight Chinese and English databases from inception to July 30, 2023, and 242 studies were retrieved. Finally, 15 randomized controlled trials (n=1076) were included in a meta-analysis using Review Manager V.5.4.1. meta-analysis results included efficacy rate, visual rating scale (VAS) for pain, serum uric acid level (SUA), immediate analgesic effect, and incidence of adverse events. Electroacupuncture (or combined non-pharmacologic) treatment of AGA was significantly different from treatment with conventional medications (RR = 1.14, 95% confidence interval CI = 1.10 to 1.19, P < 0.00001). The analgesic effect of the electroacupuncture group was superior to that of conventional Western drug treatment (MD = -2.26, 95% CI = -2.71 to -1.81, P < 0.00001). The electroacupuncture group was better at lowering serum uric acid than the conventional western drug group (MD =-31.60, CI -44.24 to -18.96], P < 0.00001). In addition, electroacupuncture combined with Western drugs had better immediate analgesic effects than conventional Western drug treatment (MD = -1.85, CI -2.65 to -1.05, P < 0.00001). Five studies reported adverse events in the electroacupuncture group versus the drug group, including 19 cases of gastrointestinal symptoms and 6 cases of neurological symptoms (RR = 0.20, 95% CI = 0.04 to 0.88, P = 0.03).